1994
DOI: 10.1093/aesa/87.5.546
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Host Exploitation by the Parasitoid Wasp Trichogramma minutum (Hymenoptera: Trichogrammatidae) when Attacking Eggs of the Spruce Budworm (Lepidoptera: Tortricidae) in Canadian Forests

Abstract: We examined patterns of host exploitation by natural populations of the parasitoid Trichogramma minutum Riley parasitizing eggs of the spruce budworm, Choristoneura fumiferana (Clemens), in Canadian boreal forests in an effort to identify aspects to improve inundative releases. Egg masses of spruce budworm were sampled from eight different sites in Ontario and New Brunswick during the period of oviposition in 1992. Parasitoids did not necessarily fully exploit a discovered egg mass; 35% of parasitized egg mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Therefore, in tlle ramaining studies, we chose to use the number of eggs parasitized per egg mass as a measure of parasitism because counting the number of parasitized eggs is easier than determining percentage parasitism in each egg mass. Similar observations were made for the relation between the number of T. minutumparasitized spruce budworm eggs and the number of eggs per egg mass (Bai and Smith 1994).…”
Section: Methodssupporting
confidence: 76%
“…Therefore, in tlle ramaining studies, we chose to use the number of eggs parasitized per egg mass as a measure of parasitism because counting the number of parasitized eggs is easier than determining percentage parasitism in each egg mass. Similar observations were made for the relation between the number of T. minutumparasitized spruce budworm eggs and the number of eggs per egg mass (Bai and Smith 1994).…”
Section: Methodssupporting
confidence: 76%
“…Lepidopteran eggs, the hosts of Trichogramma species, however, are laid either singly or in clusters that can be so large as to exceed the egg load of the parasitoids (e.g. Bai & Smith, 1994), and thus selection to avoid egg depletion appears be the most likely explanation for the variation in potential fecundity of Trichogramma species. To what extent Trichogramma species differ in host range and whether species with greater fecundities are more frequently associated with hosts that lay eggs in clusters is unknown, but may have important implications for the use of Trichogramma species in inundative biological control.…”
Section: Discussionmentioning
confidence: 99%
“…In all three Trichogramma species, oviposition rate was gradually decreased with increasing age of female wasps. According to the opinion of Bai and Smith (1994), maximum oviposition of female wasps will occur in the first day, if Trichogramma wasps possess so many hosts. Similarly, in the current research, the oviposition of wasps and subsequently the rate of parasitism (on 50 host eggs) were recorded on the first day and was found that the average number of eggs of T. pintoi was more than T. embryophagum and T. brassicae.…”
Section: Resultsmentioning
confidence: 99%